Effect of Postoperative Ocular Residual Astigmatism (ORA) on Treatment Outcome After Myopic Laser in situ Keratomileusis (LASIK) - Nöthel J; Katz T; Druchkiv V; Frings A (Clinical Ophthalmology, 2022)
Johanna Nöthel,1,* Toam Katz,1,* Vasyl Druchkiv,2 Andreas Frings3 1Department of Ophthalmology, University Medical Centre Hamburg-Eppendorf, Hamburg, Germany; 2Department of Research & Development, Clínica Baviera, Valencia, Spain; 3Department of Ophthalmology, Heinrich-Heine-University Duesseldorf, Duesseldorf, North Rhine-Westphalia, Germany*These authors contributed equally to this workCorrespondence: Johanna Nöthel, Email Noethel.johanna@gmail.comPurpose: To analyze the impact of postoperative ocular residual astigmatism (ORA) on refraction, visual acuity and subjective satisfaction after myopic laser-in-situ-keratomileusis (LASIK) by a comprehensive analysis, which includes clinically relevant data and patient-reported outcomes.Material and Methods: To evaluate the influence of ORA, comparison groups were built following Archer et al. Myopic patients were subdivided by the fraction ORA/MRC (matched and not matched for MRC) (MRC = manifest refractive cylinder), ORA magnitude and CA magnitude in high ORA eyes (CA = corneal astigmatism). Refractive and visual data were analyzed via retrospective cross-sectional analysis for multiple parameters. The subjective satisfaction was analyzed retrospectively 3– 4 years after having LASIK via patient reported outcome analysis.Results: Refractive outcome: Only when grouped by ORA magnitude only, high ORA eyes resulted in approximately twice as cylinder magnitude compared to eyes with preoperative lower ORA. Furthermore, there appeared to be no statistically significant differences in any case. Visual outcome: There appeared to be no statistically significant differences for visual acuity parameters (safety index, efficacy index). Patient reported outcome: When grouped by the rate of ORA/MRC not matching for MRC, there were statistically significant differences in the subjective satisfaction (p = 0.006) and the postoperative side effects (p = 0.001, p = 0.01, p = 0.006), those differences appeared less strong when matched for MRC treated and result better for a higher ratio of ORA/MRC.Conclusion: Patients with postoperatively high ORA report on higher satisfaction with treatment results than patients with postoperatively low ORA. This did not correlate with differences in the refractive nor visual outcome. As a matter of fact, there is a discrepancy between the objective analysis results and the subjective satisfaction of patients.Keywords: ocular residual astigmatism, myopic LASIK, refractive outcome, visual outcome, patient reported outcome